Generalized Logarithmic Divergence Measure for Intuitionistic Fuzzy Matrix - Malik, S. C.; Raj, Masum; Thakur, Rahul (Communications in Mathematics and Applications, 2023)
For solving multi-criterion decision making problems, we in this paper propose a parametric generalized logarithmic divergence measure for intuitionistic fuzzy matrices. The validity of a symmetric divergence measure has been established for the proposed measure. Also, the properties (compliment, transitivity, concavity and symmetricity) of this measure for intuitionistic fuzzy matrices are studied. Application of the proposed measure has been illustrated through a decision-making problem in trade market.